Improving Scientific Literacy of Muslim Higher Education Students through Social Media - Novitsa; Hakiman (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2024)
This paper explores social media as a means to improve the scientific literacy of Muslim higher education students. A qualitative study was conducted with data collected from interviews, observations, documentation, forum group discussion, and questionnaire. Triangulation method was used to validate the data, while interactive analysis was performed to analyze the data. This study demonstrates that Muslim higher education students were familiar in using social media to improve their knowledge regarding the inclusiveness of Islam. In this context, three major types of media were social media networks (WhatsApp and Facebook), sharing media (Instagram, YouTube, and TikTok), and blog and microblog (blog and Twitter). Nevertheless, social media brought adverse impact on the management of lecture materials, triggered self-insecurity, and spread hoax or fake news.